2011
DOI: 10.1016/j.visres.2010.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Distinct visual motion processing impairments in aging and Alzheimer’s disease

Abstract: Aging and Alzheimer's disease (AD) are associated with declines in the visual perception of self-movement that undermine navigation and independent living. We studied 214 subjects' heading direction and speed discrimination using the radial patterns of visual motion in optic flow. Young (YA), middle-aged (MA), and older normal (ON) subjects, and AD patients viewed optic flow in which we manipulated the motion coherence, spatial texture, and temporal periodicity composition of the visual display. Aging and AD w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 62 publications
3
69
3
Order By: Relevance
“…On the other hand, the de novo appearance of CMs has also been described in nonfamilial disease [104,105,106,107]. Therefore, although external factors have been suggested to be responsible for rapid or sudden changes in the behavior of CMs [108], it is reasonable to argue that genetic alteration remains the main factor influencing the appearance and growth of CMs, both in familial and nonfamilial cases. Genetic aberrations are probably the primary causative factors which, through phenotype modifications, produce altered molecules influencing the angiogenesis network in surrounding tissues [109,110,111].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the de novo appearance of CMs has also been described in nonfamilial disease [104,105,106,107]. Therefore, although external factors have been suggested to be responsible for rapid or sudden changes in the behavior of CMs [108], it is reasonable to argue that genetic alteration remains the main factor influencing the appearance and growth of CMs, both in familial and nonfamilial cases. Genetic aberrations are probably the primary causative factors which, through phenotype modifications, produce altered molecules influencing the angiogenesis network in surrounding tissues [109,110,111].…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that even young adults when provided with a bar in front when standing up, generated much higher horizontal momentum than when standing up with an empty space in front (Pai & Lee, 1994). It is also possible that presence of the table provided a visual reference point and compensated for spatial orientation and motion processing problems (Kavcic, Vaughn, & Duffy, 2011), decreased depth and contrast perception (Valenti, 2010), and balance problems, common in people living with dementia (Suttanon et al, 2012;Taylor, Delbaere, Lord, Mikolaizak, & Close, 2013).…”
Section: Variablesmentioning
confidence: 99%
“…The addition of a secondary task tends to decrease task performance more strongly in older adults than in younger adults (Bisson et al, 2014;de Dieuleveult et al, 2017;Mahboobin et al, 2007;Redfern et al, 2001Redfern et al, , 2009. It is well known that the age-related deterioration of, for instance, vision (Kavcic et al, 2011;Owsley, 2011), joint mobility (Yeh et al, 2015), muscle force (Cruz-Jentoft et al, 2010), and balance (Teasdale et al, 1991) all decrease performance of the activities of daily living. How changes in sensory integration influence age-related decline in activities of daily living is less well researched.…”
Section: Introductionmentioning
confidence: 99%
“…Vision guides goal-directed reach movements towards moving targets (Brenner and Smeets, 2015;Brouwer et al, 2002Brouwer et al, , 2003Kavcic et al, 2011). When judging the target's motion, one could simply rely on the target's retinal slip together with extra-retinal information about eye, head and body movements, but one might be able to improve the precision by assuming that the environment is stable.…”
Section: Introductionmentioning
confidence: 99%